Using Swift : transitioning from Objective-C - Lee, Keith; Safari eBooks ([New York] : Apress, 2015)
"Developing apps for Apple's broadening platform of devices is an exciting topic these days. Apple created the Swift programming language to build state-of-the-art apps using the latest Apple technologies. In this video course the similarities and differences between traditional Objective-C based programming and Swift are revealed. You'll learn how to apply your Objective-C skills to successfully transition to programming in Swift. Using Swift: Transitioning from Objective-C reaches out to all developers who are interested in creating state-of-the-art apps for Apple's broadening platform of devices. This video course prepares developers for building the next generation of apps in Swift to surprise and delight users the world over."--Resource description page.
Title from resource description page (viewed June 18, 2015).
Presenter, Keith Lee.
Place of publication from publisher's website.
Keywords: Programming languages (Electronic computers); Application software -- Development; Objective-C (Computer program language); Electronic books